Targeting the B-cell receptor pathway: a review of current and future therapies for non-Hodgkin's lymphoma. (3rd April 2018) - Rodgers, Thomas D.; Reagan, Patrick M.
ABSTRACT: Introduction : The B-cell receptor (BCR) pathway is a crucial aspect of mature lymphocytes and is maintained in B-cell neoplasms. Many small module inhibitors targeting kinases within the BCR pathway are approved, with others in development, offering alternative treatment options to standard chemoimmunotherapy. Areas covered : This review covers both approved inhibitors and investigational inhibitors of spleen tyrosine kinase (SYK), Bruton's tyrosine kinase (BTK), and phosphoinositide-3-kinase (PI3K) in the treatment of B-cell lymphomas. To collect relevant articles, a literature search was completed through the use of PubMed and abstracts from ASH and ASCO national meetings. Search terms including non-Hodgkin lymphoma, and BCR inhibitors, as well as the individual drug names, were utilized. The majority of included studies are dated from 2012 to March 2018. Expert opinion : BCR pathway inhibitors, such as ibrutinib and idelalisib, are novel treatments for non-Hodgkin lymphomas. While providing alternative treatment options to those with high-risk disease, poor functional status, and relapsed disease, outside of chronic lymphocytic leukemia (CLL), they have been limited to the relapsed/refractory setting. Their mechanisms of action, off/on-target effects, and resistance patterns create unique therapeutic dilemmas. It is our opinion that more specific inhibitors, as well as combination therapy, will define the future for BCR inhibitors.